Optimising governance capabilities for science, research and innovation in Africa. (February 2022) - Mugwagwa, Julius; Banda, Geoffrey; Ozor, Nicholas; Bolo, Maurice; Oriama, Ruth
Abstract: This article discusses empirical challenges and opportunities for African countries in their quest to have sustainable mechanisms for funding research and innovation. Like elsewhere in different parts of the world, African countries have been exploring different approaches, institutional reforms, models and mechanisms towards more efficient and effective funding and financing of research and innovation to enhance their individual and collective economic development aspirations. This paper derives from a 2018 to 2019 study which used a combination of primary and secondary data sources to inform current debates and reviews on the re- organization of research and innovation funding in Africa. Attempts to copy experiences of high income economies in harnessing and deploying funding mechanisms into national research and innovation systems are not appropriate if not accompanied by adaptation to systemic and contextual aspects in receiving countries and sectors. This paper presents and analyses recent empirical evidence from 15 African countries to argue that successful adaptations are not just a matter of technological and innovation capabilities, timely and adequate resourcing, but are a function of decision-making and governance capabilities, which in turn arise from deliberate and interactive learning across the entire research and innovation system. This work contributes to some of the themes covered in this journal recently on the broad issue of resources for innovation, including financial and relational resources. Highlights: Besides the current COVID-19 pandemic, African countries have many economic development challenges and opportunities to deal with. New knowledge from research and innovation seen as key drivers in these, but these drivers need resources. Different ways of funding research and innovation have been deployed, but some shortcomings remain, with respect to, inter alia, consistency of the funding, sufficiency of the funding and relevance of the funding. This paper presents and analyses recent empirical evidence from 15 African SGCI countries to argue that successful adaptations are not just a matter of timely and adequate resourcing, or technological and innovation capabilities. Decision-making and governance capabilities, which arise from deliberate and interactive learning across entire research and innovation systems, are also key.